Language-mixing in Content and Language Integrated Learning: benefit or burden? An auditory recall perspective - Caira, Thomas; Declerck, Mathieu; Struys, Esli (Frontiers in Education, 2025)
Recent pedagogical trends have seen a revival in language-mixing in CLIL contexts, thereby challenging the traditional ‘one subject-one language’ approach. From a cognitive standpoint, recent research indicates that the disadvantages of language mixing may not be as significant as previously thought. This is further supported by studies showing no negative effects of language-mixing on immediate memory recall in CLIL pupils. Using an Old/New recognition task design, participants in the present study had to differentiate between previously defined concepts and new ones in three different language contexts (i.e., single-language L1; single-language L2 and a mixed context). We also accounted for delayed recall with a second test phase 36 hours after the first one. Response times and accurate recall scores were retained for further analysis. Our findings reveal a nuanced picture: we found that mixed-language input negatively impacts immediate and delayed recall of information compared to L1 input. However, mixed-language input also brings about better recall of information compared to L2 input. It seems that language-mixing thus partly mitigates the disadvantage in auditory recall that occurs in a single-language L2 context. Overall, these results suggest a need to reconsider the effects of language-mixing on memory and, consequently, nuance its role in CLIL practices.